Evaluasi keberadaan FMA di lahan pasca tambang peti untuk meningkatkan rehabilitasi dengan potensi fitoremediasi - Hamzah; Rumondang, Jenny; Puri, Suci Ratna; Handayani, Rajjitha; Hardiyanti, Rizky Ayu; Rif'atunidaudina, Ria (Proceedings Academic Universitas Jambi, 2025)
Illegal gold mining (PETI) activities have caused significant land degradation, particularly affecting the physical and chemical properties of the soil. This study aims to identify the presence of Arbuscular Mycorrhizal Fungi (AMF) in former illegal gold mining sites (PETI) and evaluate their potential to support land rehabilitation through a phytoremediation approach. Soil samples were purposively collected from PETI sites based on the year the mining began (2019, 2020, 2021), as well as from control sites, under the canopy of phytoremediating plants such as Melastoma malabathricum, Chromolaena odorata, and Cyperus odoratus. Laboratory analysis revealed that the soil texture was dominated by clay fractions (>40%), which negatively affected soil porosity and nutrient availability. AMF identification showed the highest spore count in 2020 (73 spores/50 g soil), particularly in soils associated with the roots of Melastoma malabathricum. These findings indicate that AMF play a crucial role in supporting the adaptation of hyperaccumulator plants and enhancing nutrient uptake in degraded soils. The symbiosis between AMF and phytoremediating plants presents an effective and ecologically sustainable strategy for rehabilitating post-mining land.